Digital health evaluation workshop for interprofessional healthcare students - Timothy Dy Aungst; Monina R Lahoz; Paula J Evans (Digital Health, 2017)
The use of online resources by patients for their daily health needs has escalated with the proliferation of mobile devices and mobile apps. While healthcare professionals can help their patients access quality online resources and tools, they may not have received the education and training to do this effectively. To meet this educational need, a daylong workshop was developed at a health sciences university that aimed to increase awareness of students in various health disciplines of mobile health-related apps and federally sponsored websites that provide patient-friendly medical information.